Effect of X- irradiation on the state of the antioxidant defense system and lipid peroxidation (Experimental biology, 2016)
The increasing use of radioactive isotopes in the industry and , mainly in nuclear power are at greatest risk exposure of those professionally in contact with sources of ionizing radiation . At present, the study of lipid peroxidation ( LPO) and its regulation systems is becoming increasingly urgent , highlighting the problem of finding effective means of correcting the antioxidant status of the organism. We have studied the intensity of endogenous lipid peroxidation in rat liver tissue . It is shown that the level of primary and secondary products of lipid peroxidation in tissues of experimental animals indicate that the activation of lipid peroxidation in different periods after radiation exposure. The accumulation of lipid peroxidation products in the first place indicates both the intensification of oxidative processes in the body, and to reduce the antioxidant status, namely enzymatic and non-enzymatic antioxidant defense units.
Keywords: gamma - irradiation; antioxidants; spectrophotometer; radiation; oxidation; status; organism; lipids.